Indigenous and faith healing in Ghana: A brief examination of the formalising process and collaborative efforts with the biomedical health system - Lily Kpobi; Leslie Swartz (AOSIS, 2019)
Background: Health seeking in many African countries typically involves making use of multiple healing systems, including indigenous and faith systems, as well as biomedical healthcare systems. These different systems have co-existed for many years in Africa, including in Ghana. Aim: In this article, we examine the formalising processes that non-biomedical healthcare in Ghana has undergone in postcolonial times. We first present a brief historical analysis of the process of organising indigenous medical systems into formal bodies. We then conclude by exploring collaborative efforts that have been undertaken between biomedical and non-biomedical health systems in Ghana. Method: A historical analysis of formalised indigenous healing systems in Ghana was done through an examination of relevant literature. Results: Formal groups of indigenous healers in Ghana who are organised into specific categories have undergone various transformations over the years. Evidence also exists of collaborative programmes developed with traditional healers in Ghana, although these have been largely for primary health partnerships. With regard to mental health collaborations, attempts at integration have been generally unsuccessful, with various factors identified as hindering successful partnerships. Conclusion: Indigenous healing is an important component of healthcare in Ghana. Collaboration between the different healthcare systems can be strengthened through accurate understandings of how key stakeholders are situated (and indeed situate themselves) in the conversation.